Association Between Knowledge of Condom Functions and Condom Use among Sexually-Active Unmarried Male Adolescents in Indonesia - Rahmartani, Lhuri Dwianti; Adisasmita, Asri (Jurnal Epidemiologi Kesehatan Indonesia, 2018)
Background: Premarital sex is culturally unacceptable in Indonesia and education on safe sex practice remains controversial. Meanwhile, Indonesia Demographic and Health Surveys (IDHS) show gradual increase in the prevalence of sexually-active adolescents nationwide, particularly among unmarried males. Unfortunately, condom use is low among this population and it is unclear whether it relates to inadequate knowledge on safe sex practice including condoms. Objective: to see whether there is an association between knowledge on condom functions and condom use among adolescents.Method: cross-sectional study of 913 Indonesian unmarried males aged 15 – 24 who have had sex (IDHS Adolescent Reproductive Health 2012 dataset). The independent variable is knowledge on condom functions while the dependent variable is the use of condoms. Statistical analysis is performed using Chi Square and Cox regression.Result: The prevalence of condom use is about twice higher in respondents with sufficient knowledge on condom functions (31%), than in respondents without (15.1%); adjusted PR 2.38 (95%CI 1.47 3.85). Conclusion: Having knowledge about condoms is positively associated with safer sex practice among sexually active adolescents. Banning information on condoms may place sexually-active adolescents into unprotected sex. Education on safe sex practice is needed but should be cautiously tailored to meet cultural values